Pola Pertumbuhan Mangrove Jenis (Bruguiera gymnorrhiza) dan (Ceriops tagal) dengan Metode Pembibitan menggunakan Substrat yang Berbeda di Pulau Serangan, Denpasar, Bali - Alvin Agus Prambudy; I Wayan Restu; Ni Putu Putri Wijayanti (Current Trends in Aquatic Science, 2023)
This research was conducted to determine the growth pattern and percentage of survival as well as the growth rate of mangrove species Bruguiera gymnorrhiza and Ceriops tagal per unit time using different types of substrates This study used a completely randomized design (CRD) with five treatments) by 5 technique for example, Handling A with 100% sand substact, Handling B with 100% soil substract, Handling C with 50% soil and sand substract, Handling D with 30% sand and 70% soil substract, and Handling E with 70% sand and 30% soil substract, and 10 repetitions. Measurements were carried out every week starting after 1 week of planting for 2 months. Parameters observed were plant height, plant diameter, number of leaves, mangrove survival and mangrove growth rate. Quantitative data were analyzed statistically by ANOVA. The results of Bruguiera gymnorrhiza species has height between 8,87-27,88 cm, growth rate range 1,11-1,17 cm/week, diameter of growth 0,07-0,14 cm, and number of leaves as much 3-5 sheet, while mangrove results of Ceriops tagal has height between 0,76-1,42 cm, growth rate range 0,10-0,18 cm/week, diameter of growth 0,02-0,08 cm, and number of leaves as much 1-2 sheet for 8 weeks. The results showed that mangrove nurseries using a combination of substrates did not give a significant difference to the growth pattern, survival percentage and mangrove growth rate.